Pemetaan Zona Potensi Air Tanah Untuk Mengatasi Kekeringan Di Desa Tuabatan Kecamatan Miomaffo Tengah Kabupaten Timor Tengah Utara - Anjelika Banafanu; Arfita Rahmawati; Tugma Jaya Manalu (Universitas Negeri Gorontalo, 2025)
Tuabatan Village frequently experiences droughts, which impact clean water availability. This study aims to map groundwater potential zones as a solution to address this drought. The method used was quantitative analysis with a remote sensing approach, utilizing Sentinel-2 satellite imagery to calculate the Normalized Difference Water Index (NDWI). Primary data was obtained through field observations at 13 water sample points, while secondary data included satellite imagery and administrative maps. The analysis classified the study area into three groundwater potential zones based on the NDWI value range : high zone (0,13 to 0,37) covering an area of 124,11 hectares (27,87%), medium zone (0 to 0,13) covering an area of 214,11 hectares (48,09%), and low zone (-0,24 to 0) covering an area of 107 hectares (24,04%).